2004
DOI: 10.1007/s00114-004-0562-4
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of mesophilic, oxalate-degrading Streptomyces from plant rhizosphere and forest soils

Abstract: The present work was aimed at the isolation of additional new pure cultures of oxalate-degrading Streptomyces and its preliminary characterization for further work in the field of oxalate metabolism and taxonomic studies. Mesophilic, oxalate-degrading Streptomyces were enriched and isolated from plant rhizosphere and forest soil samples. Strains were examined for cultural, morphological (spore chain morphology, spore mass colour, diffusible and melanin pigment production), physiological (antibiosis, growth in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Alpha-, beta-, and gammaproteobacteria correspond to a large fraction of the known culturable oxalotrophic diversity previously described (Sahin et al 2002;Tamer et al 2002;Sahin 2003;Sahin et al 2008). Oxalotrophic activity has been also reported in previous studies in Firmicutes (Turroni et al 2007), Actinobacteria (Müller 1950;Knutson et al 1980;Sahin 2004), and among diverse diazotrophic bacteria (Trinchant and Rigaud 1996;Sahin 2005). However, in this study, we report a diverse assemblage of bacterial species.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Alpha-, beta-, and gammaproteobacteria correspond to a large fraction of the known culturable oxalotrophic diversity previously described (Sahin et al 2002;Tamer et al 2002;Sahin 2003;Sahin et al 2008). Oxalotrophic activity has been also reported in previous studies in Firmicutes (Turroni et al 2007), Actinobacteria (Müller 1950;Knutson et al 1980;Sahin 2004), and among diverse diazotrophic bacteria (Trinchant and Rigaud 1996;Sahin 2005). However, in this study, we report a diverse assemblage of bacterial species.…”
Section: Discussionsupporting
confidence: 72%
“…So far, 54 phylogenetically non-related cultivable species of oxalotrophic bacteria, and in particular Azospirillum (Sahin 2004) and Methylobacterium (Sahin et al 2008), have been reported in Mediterranean niches (Sahin 2003). Some genera such as Pseudomonas, Xanthobacter, and Burkholderia have been identified as oxalotrophs as well (Tamer et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…(strain BV1M3), isolated from a tropical soil, has also a large activity when grown on Kox as sole carbon source (consumption rate of 0.26 μM h −1 ; (Bravo et al ., ). Many studies on the role of Actinobacteria as oxalotrophic bacteria have been primarily concerned with the enumeration and taxonomy of Streptomyces (Lechevalier & Lechevalier, ; Sahin, , ). This group is known to be saprophyte (Goodfellow & Williams, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, calcium oxalate is readily decomposed by oxalotrophic bacteria (Knutson et al 1980; Sahin 2004; Martin et al 2012). The bark of Scots pine that initially hosted the oxalate crystals is resistant to microbial degradation.…”
Section: Resultsmentioning
confidence: 99%